Effectiveness of Mind Mapping Recording Model To Improve Students' Motivation and Understanding Of Class VII-2 At SMPS IT Yayasan Pendidikan Tarbiyah Islamyah Lubuk Cemara Perbaungan - Hidayat, Nazwin; Lestari, Vika; Kirana, Rika Dani; Laila, Henni; Rohani, Siti (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the effectiveness of the mind mapping recording model in improving the motivation and understanding of class VII-² students at the Integrated Islamic Private Junior High School of the Tarbiyah Islamiyah Education Foundation, Lubuk Cemara Perbaungan. Mind mapping was chosen as a recording model because it is considered to make it easier for students to organize information and improve memory. This study used an experimental method with a pre-test and post-test design to determine the changes that occurred in students after the application of the mind mapping model. The subjects of the study consisted of 30 students who were selected randomly. Data were collected through a questionnaire used to measure students' learning motivation, as well as a test to measure students' understanding of the subject matter. Data analysis was carried out by comparing the results of the pre-test and post-test, as well as changes in the motivation questionnaire scores before and after treatment. The results showed that the application of the mind mapping model can significantly increase students' learning motivation and also improve their understanding of the material being taught. Based on these findings, it can be concluded that the use of the mind mapping model is an effective strategy to improve students' motivation and understanding, especially in subjects that require clear and structured information organization